2020
DOI: 10.1007/s00702-020-02285-w
|View full text |Cite
|
Sign up to set email alerts
|

Adult attention-deficit/hyperactivity disorder symptoms, cognitive dysfunction and quality of life in high-dose use of benzodiazepine and Z-drug

Abstract: High-dose use of benzodiazepines (BZDs) and Z-drugs was found to be associated with adult attention deficit/hyperactivity disorder (ADHD) and multidomain cognitive deficits, but the interplay between these factors and its effect on quality of life (QoL) is unclear. We explored (a) whether cognitive dysfunction differs in high-dose BZD/Z-drug users with and without adult ADHD and (b) the impact of cognitive deficits and adult ADHD on QoL in this substance-use disorder (SUD). From January 2015 to December 2019, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 58 publications
0
5
1
Order By: Relevance
“…BDZ-induced neurocognitive deficit seems to persist even following the suspension of BDZ [36,37]. It has been suggested that the clinical impact of the long-term use of BDZ may be even higher in ADHD subjects [38]. In addition, in the present study, HUD/A-ADHD patients treated with D&N AOT seem to have results that differ from those obtained in an Italian polycentric study [39].…”
Section: Demographic Clinical and Treatment Outcome Characteristics According To The Presence Of Adhd Symptomatologycontrasting
confidence: 77%
“…BDZ-induced neurocognitive deficit seems to persist even following the suspension of BDZ [36,37]. It has been suggested that the clinical impact of the long-term use of BDZ may be even higher in ADHD subjects [38]. In addition, in the present study, HUD/A-ADHD patients treated with D&N AOT seem to have results that differ from those obtained in an Italian polycentric study [39].…”
Section: Demographic Clinical and Treatment Outcome Characteristics According To The Presence Of Adhd Symptomatologycontrasting
confidence: 77%
“…Benzodiazepines were also commonly used by respondents with psychiatric symptoms. In a small patient cohort using high-dose benzodiazepines, those with ADHD performed worse in cognitive function and had lower quality of life (Federico et al, 2021). Kratom, especially in lower doses (Warner et al, 2016), may be used as a stimulant self-treatment to mitigate ADHD symptoms and benzodiazepine adverse effects.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the increased risk of falls, care is recommended when using BZDs in elderly subjects ( 27 ). As ADHD is often associated with sleep disturbance, caution should also be taken when prescribing BZDs or ZDs in people with ADHD ( 105 ). Furthermore, BZDs may lower the threshold for suicidal behavior in patients with depression ( 71 ).…”
Section: Discussionmentioning
confidence: 99%